2006
DOI: 10.1038/sj.bjc.6603120
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lymphangiogenesis to prevent tumour metastasis

Abstract: Recent studies involving animal models of cancer and clinicopathological analyses of human tumours suggest that the growth of lymphatic vessels (lymphangiogenesis) in or nearby tumours is associated with the metastatic spread of cancer. The best validated molecular signalling system for tumour lymphangiogenesis involves the secreted proteins vascular endothelial growth factor-C (VEGF-C) and VEGF-D that induce growth of lymphatic vessels via activation of VEGF receptor-3 (VEGFR-3) localised on the surface of ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
120
0
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 56 publications
2
120
0
8
Order By: Relevance
“…These high interstitial pressures are due in part to the lack of functional lymphatics within the tumor [47] and result in a net convective flow out from the tumor mass into the surrounding tissue as a result of the lower interstitial pressure found there. (The conclusion that tumors lack functional lymphatics is controversial, however; several reports have suggested that metastatic tumors can induce lymphatic growth into the tumor mass [48]. )…”
Section: Interstitial Flow In Cancermentioning
confidence: 99%
“…These high interstitial pressures are due in part to the lack of functional lymphatics within the tumor [47] and result in a net convective flow out from the tumor mass into the surrounding tissue as a result of the lower interstitial pressure found there. (The conclusion that tumors lack functional lymphatics is controversial, however; several reports have suggested that metastatic tumors can induce lymphatic growth into the tumor mass [48]. )…”
Section: Interstitial Flow In Cancermentioning
confidence: 99%
“…The spread of tumor cells to regional lymph nodes through the lymphatic system plays a central role in the dissemination of various human cancers such as breast cancer (Achen et al, 2006). Experimental tumor models and human clinicopathologic data indicate that lymphangiogenesis and lymph node metastasis are important prognostic indicators for the spread of cancer (Eccles et al, 2007;Miyahara et al, 2007).…”
mentioning
confidence: 99%
“…3,30 In many animal models of cancer, VEGF-C has been shown to enhance tumor lymphangiogenesis, the metastatic spread of tumor cells to lymph nodes and, in some cases, distant organ metastasis. 31 Downregulation of VEGF-C using siRNA has been shown to reduce lymph node and lung metastases in murine mammary cancer models. 11 In addition, VEGFR-3, the VEGF-C receptor, is predominantly expressed on lymphatic endothelial cells, 32 and VEGF-C-dependent activation of VEGFR-3 stimulates the growth of lymph endothelial cells and lymphatics.…”
mentioning
confidence: 99%